Pengaruh Gaya Kepemimpinan Dan Iklim Organisasi Kepada Perilaku Kerja Inovatif - Zulkifli Zulkifli; Almansyah Rundu Wonua; Niar Astaginy (BENING, 2026)
This study seeks to analyze the impact of leadership style and organizational climate on innovative work behavior at the Kolaka Regency Tourism Office. Using a quantitative approach, data were gathered through questionnaires. The research involved all 36 employees of the Kolaka Regency Tourism Office, with the entire population selected as the sample through the census (saturated) sampling method. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) via SmartPLS 3.0. The results show that both leadership style and organizational climate have a positive and significant influence on innovative work behavior.